KINERJA PT. JASA RAHARJA (PERSERO) DI JAWA TENGAH (2012-2014) - Juli Franinta Siregar; Drs. Purwoko, M.S Drs. Purwoko, M.S; Dra. Sulistyowati, M.Si Dra. Sulistyowati, M.Si (Journal of Politic and Government Studies, 2015)
Traffic accidents are a global public health  problem that is faced by all countries in the world,  especially developing countries.  This is certainly the high number of accidents  caused by many factors, either because of human  error (human error), technical errors, and nature. In  Indonesia, the biggest cause of accidents caused by human error, which reached 90%. When you  look at these facts, it should have the potential for a  reduced number of accidents, due to human error  factor is a factor that can be prevented by humans.The presence of PT JasaRaharja (Persero) as  insurance Indonesian Society, provide protection  to the public During the period of 54 years, PT JasaRaharja (Persero) is able to be a friend of the community. The main function of implementing and supporting the government's policy program in the field of national economic development, especially to improve the welfare of the people through the implementation of social insurance in accordance with JasaRaharjathe tagline "insurance Indonesian Community". The company looked at the sustainability of the company's business is realized by improving the quality of care and social insurance benefits to meet the needs of an increasingly complex and varied. The Company believes the increase in quality of service and increased insurance benefits can add value to the lives and welfare of the community in the face of various socio-economic risks.During the period of 54 years, PT JasaRaharja (Persero) is able to be a friend of the community. The main function of implementing and supporting the government's policy program in the field of national economic development, especially to improve the welfare of the people through the implementation of social insurance in accordance with JasaRaharjathe tagline "insurance Indonesian Community". The company looked at the sustainability of the company's business is realized by improving the quality of care and social insurance benefits to meet the needs of an increasingly complex and varied. The Company believes the increase in quality of service and increased insurance benefits can add value to the lives and welfare of the community in the face of various socio-economic risks.Through its related agencies such as police and hospitals, accident insurance program and insurance passenger traffic accidents held above the law provide a strong foundation for PT JasaRaharja (Persero) to protect the overall public transport passengers and road users of the risks of accidents that always haunt and cause catastrophe.